An Intersectional Approach to Target Neural Circuits With Cell- and Projection-Type Specificity: Validation in the Mesolimbic Dopamine System - Kakava-Georgiadou, Nefeli; Zwartkruis, Maria M.; Bullich-Vilarrubias, Clara; Luijendijk, Mieneke C. M.; Garner, Keith M.; van der Plasse, Geoffrey; Adan, Roger A. H. (Frontiers in Molecular Neuroscience, 2019)
Development of tools to manipulate activity of specific neurons is important for dissecting the function of neural circuits. Viral vectors and conditional transgenic animal lines that target recombinases to specific cells facilitate the successful manipulation and recording of specific subsets of neurons. So far, it has been possible to target neuronal subtypes within a certain brain region based on transcriptional control regions from a gene selectively expressed in those cells or based upon its projections. Nevertheless, there are only a few tools available that combine this and target a neuronal subtype within a projection. We tested a viral vector system, consisting of a canine adenovirus type 2 expressing a Cre-dependent Flp recombinase (CavFlexFlp) and an adeno-associated viral (AAV) vector expressing a Flp-dependent cDNA, which targets neurons in a subtype- and projection-specific manner. As proof of principle we targeted expression of a Designer Receptor Exclusively Activated by Designer Drugs (DREADD) to the dopamine neurons of the mesolimbic projection, which allows the transient activation of neurons by the ligand Clozapine-N-Oxide (CNO). We validated that the system specifically targets dopamine neurons and that chemogenetic activation of these neurons induces an increase in locomotor activity. We thus validated a valuable tool that allows in vivo neuronal activation in a projection- and subtype-specific manner.